# Example 37

Last updated at Feb. 13, 2018 by Teachoo

Last updated at Feb. 13, 2018 by Teachoo

Transcript

Example 37 (Method 1)Find ππ¦/ππ₯ , if π₯^(2/3) + π¦^(2/3) = π^(2/3) . π₯^(2/3) + π¦^(2/3) = π^(2/3) Differentiating w.r.t. x (π(π₯^(2/3)))/ππ₯ + (π(π¦^(2/3)))/ππ₯ = (π(π^(2/3)))/ππ₯ 2/3 π₯^(2/3 β 1) + (π(π¦^(2/3)))/ππ₯ Γ ππ¦/ππ¦ = 0 2/3 π₯^((β1)/3) + (π(π¦^(2/3)))/ππ¦ Γ ππ¦/ππ₯ = 0 2/3 π₯^((β1)/3) + 2/3 π¦^(2/3 β 1) Γ ππ¦/ππ₯ = 0 2/3Γ1/π₯^(1/3) + 2/3 y^((β1)/3) Γ ππ¦/ππ₯ = 0 2/3Γ1/π₯^(1/3) + 2/3 Γ 1/π¦^(1/3) Γ ππ¦/ππ₯ = 0 2/3Γ1/π¦^(1/3) Γ ππ¦/ππ₯ = 0 β 2/3Γ 1/π₯^(1/3) 2/3Γ1/π¦^(1/3) Γ ππ¦/ππ₯ = (β2)/3Γ1/π₯^(1/3) 1/π¦^(1/3) Γ ππ¦/ππ₯ = (β1)/π₯^(1/3) ππ¦/ππ₯ = β π¦^(1/3)/π₯^(1/3) π π/π π = β (π/π)^(π/π) Example 37 (Method 2)Find ππ¦/ππ₯ , if π₯^(2/3) + π¦^(2/3) = π^(2/3) . π₯^(2/3) + π¦^(2/3) = π^(2/3) π₯^(2/3) + π¦^(2/3) = π^(2/3) . 1 π₯^(2/3) + π¦^(2/3) = π^(2/3) . (sin^2β‘π+cos^2β‘π ) π₯^(2/3) + π¦^(2/3) = π^(2/3) sin^2β‘π+π^(2/3) cos^2β‘π Let π^(π/π) = π^(π/π) γπππγ^πβ‘π½ Cubing both sides π₯^(2/3 \ Γ 3) = π^(2/3 Γ 3) (cos^2β‘π )^3 π₯^2 = π^2 cos^6β‘π x = π cos3 π Let π^(π/π) = π^(π/π) γπ¬π’π§γ^πβ‘π½ Cubing both sides π¦^(2/3 \ Γ 3) = π^(2/3 Γ 3) (sin^2β‘π )^3 π¦^2 = π^2 sin^6β‘π y = a sin3 π Let π₯ = a cos^3β‘π & π¦ = a sin^3β‘π Putting values of x and y in L.H.S of equation Solving LHS π₯^(2/3) + π¦^(2/3) = (a cos^3β‘π )^(2/3) + (a sin^3β‘π )^(2/3) = a^(2/3) cos^(3 Γ 2/3)β‘π + a^(2/3) sin^(3 Γ 2/3)β‘π = a^(2/3) cos^2β‘π + a^(2/3) sin^2β‘π = a^(2/3) (cos^2β‘π+sin^2β‘π ) = a^(2/3) . 1 = a^(2/3) = R.H.S Hence it is proved that π₯ = a cos^3β‘π & π¦ = a sin^3β‘π Now, ππ¦/ππ₯ = ππ¦/ππ₯ . ππ/ππ = ππ¦/ππ . ππ/ππ₯ = (ππ¦/ππ)/(ππ₯/ππ). Calculating π π/π π½ π¦ = a sin^3β‘π ππ¦/ππ = π(a sin^3β‘π )/ππ₯ ππ¦/ππ = a 3 sin^(3 β 2)β‘π . π(sinβ‘π )/ππ₯ ππ¦/ππ = 3π sin2 π cos π Calculating π π/π π½ π₯ = a cos^3β‘π ππ₯/ππ = (π (γa cosγ^3β‘γπ)γ)/ππ ππ₯/ππ = 3a cos^(3 β1)β‘π (π (πππ π½) )/π π½ ππ₯/ππ = 3a cos^2β‘π . (βsinβ‘π ) ππ₯/ππ = β3a π ππβ‘π cos^2β‘π Therefore ππ¦/ππ₯ = ππ¦/ππ Γ· ππ₯/ππ = (3a sin^2β‘π cosβ‘π)/(β3a cos^2β‘π sinβ‘π ) = (βsinβ‘π)/cosβ‘π = βtan π β΄ ππ¦/ππ₯ = βtan π Finding value of tan π π¦/π₯ = (π sin^3β‘π)/(π cos^3β‘π ) (π sin^3β‘π)/(π cos^3β‘π ) = π¦/π₯ sin^3β‘π/cos^3β‘π = π¦/π₯ (sinβ‘π/cosβ‘π )^3 =π¦/π₯ sinβ‘π/cosβ‘π = (π¦/π₯)^(1/3) tanβ‘π = β(π¦/π₯) Thus, ππ¦/ππ₯ = βtan π π π/π π = ββ(π&π/π)

Example 1

Example 2

Example 3

Example 4

Example 5

Example 6

Example 7

Example 8

Example 9

Example 10

Example 11

Example 12

Example 13

Example 14

Example 15

Example 16

Example 17

Example 18

Example 19

Example 20

Example 21

Example 22

Example 23

Example 24

Example 25

Example 26

Example 27

Example 28

Example 29

Example 30

Example 31

Example 32 Important

Example 33 Important

Example 34

Example 35

Example 36

Example 37 You are here

Example 38

Example 39

Example 40

Example 41 Important

Example 42 Important

Example 43

Example 44 Important

Example 45 Important

Example 46

Example 47 Important

Example 48

About the Author

CA Maninder Singh

CA Maninder Singh is a Chartered Accountant for the past 8 years. He provides courses for Practical Accounts, Taxation and Efiling at teachoo.com .